The neuropharmacology of cannabinoid receptor ligands in central signaling pathways. (5th December 2020) - Brunt, Tibor M.; Bossong, Matthijs G.
Abstract: The endocannabinoid system is a complex neuronal system involved in a number of biological functions, like attention, anxiety, mood, memory, appetite, reward, and immune responses. It is at the centre of scientific interest, which is driven by therapeutic promise of certain cannabinoid ligands and the changing legalization of herbal cannabis in many countries. The endocannabinoid system is a modulatory system, with endocannabinoids as retrograde neurotransmitters rather than direct neurotransmitters. Neuropharmacology of cannabinoid ligands in the brain can therefore be understood in terms of their modulatory actions through other neurotransmitter systems. The CB1 receptor is chiefly responsible for effects of endocannabinoids and analogous ligands in the brain. An overview of the neuropharmacology of several cannabinoid receptor ligands, including endocannabinoids, herbal cannabis and synthetic cannabinoid receptor ligands is given in this review. Their mechanism of action at the endocannabinoid system is described, mainly in the brain. In addition, effects of cannabinoid ligands on other neurotransmitter systems will also be described, such as dopamine, serotonin, glutamate, noradrenaline, opioid, and GABA. In light of this, therapeutic potential and adverse effects of cannabinoid receptor ligands will also be discussed. Abstract : The endocannabinoid system is a modulatory system, with endocannabinoids as retrograde neurotransmitters. Neuropharmacology of cannabinoid ligands in the brain can therefore be understood in terms of their modulatory actions through other neurotransmitter systems. An overview of the neuropharmacology of several cannabinoid receptor ligands, including endocannabinoids, herbal cannabis, and synthetic cannabinoid receptor ligands is given in this review. Their mechanism of action at the endocannabinoid system is described and effects of cannabinoid ligands on other neurotransmitter systems will be described.